Pengaruh Terapi Berpikir Positif, Cognitive Behavior Therapy (CBT), Mengelola Hidup dan Merencanakan Masa Depan (MHMMD) terhadap Penurunan Kecemasan Karir pada Mahasiswa Universitas Mulawarman - Adriansyah, Muhammad Ali; Rahayu, Dian; Prastika, Netty Dyan (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2015)
Anxiety career is a form of response negative which includes a feeling of fear and concerns about the availability of job opportunities which could deny fulfill the needs is intended to transform the state of a better life. Research aims to understand the decline in anxiety future career in college students after received therapy positive mind, cognitive behavior therapy (CBT) and manage to live and plan for the future training (MLPF). The study sample this is a student who experienced anxiety career a high degree of as many as 45 college students. The result showed (1) There was a difference in anxiety careers in a college student who has received special treatment cognitive behavior therapy with t = 2,067, sig = 0.048 0.050 and mean = 12 733. (2) There was a difference in anxiety careers in a college student who has received special treatment manage to live and plan for the future training (MLPF) with t = 3,366, sig = 0.002 0.050 and mean = 15,200. (3) There was no difference in anxiety careers in in a college student who has received special treatment positive thinking therapy with t = 1.807, sig = 0.082 0.050 and mean = 6533. (4) Manage to live and plan for the future training (MLPF) was more effective to reduce anxiety careers with a mean difference of 15.200 (MLPF), 12.733 (CBT), and 6.533 (positive thinking therapy).